Maxillary lateral incisor agenesis and microdontia: Minimally invasive symmetric and asymmetric esthetic rehabilitation - Lopes-Rocha,Lígia (2022)
Abstract Maxillary lateral incisor agenesis is a condition that significantly compromises smile esthetics, which is particularly worrying in young patients. This article shows how the combination of non-invasive treatments and current restorative options may improve clinical outcomes following orthodontic treatment for symmetric and asymmetric maxillary lateral incisor agenesis and microdontia. Teeth were treated with conservative resin restorations in three separate cases: two of congenitally missing maxillary lateral incisors (i.e., unilateral and bilateral) and one of microdontia. After presenting the clinical results, this article summarizes how bleaching, enameloplasty, and bonding with composite resin can enhance esthetics and functions following orthodontic space closure. The cases reveal that carefully planned, methodically executed orthodontic and restorative approaches can achieve predictable, esthetic outcomes that will improve the patient’s self-esteem with a minimally invasive solution.